Biopsy-diagnosed renal granuloma after intravesical bacillus Calmette-Guérin therapy for bladder carcinoma: a case series and review of the literature - Narita, Keiichi (BJR Case Rep, 2019)
Renal granuloma is a rare complication affecting the kidneys after intravesical bacillus Calmette-Guérin (BCG) therapy for bladder carcinoma. Our case series review describes the imaging and histopathological findings of BCG-induced renal granulomas. All three renal granulomas, which were located in the upper pole, had a solitary mass-like appearance. The mean diameter was 31.3 mm. In the two cases, the lesion was homogeneously enhanced on post-contrast CT, and presented homogeneous low signal intensity on T(2) weighted imaging (T(2)WI) and iso-signal intensity on diffusion-weighted imaging (DWI). Both lesions had increased fludeoxyglucose (FDG) uptake. Histological examinations revealed granulomatous inflammation with fibrosis. The third case showed a lesion having heterogeneous enhancement on CT, heterogeneous and slightly high signal intensity on T(2)WI, and high signal intensity on DWI. This case showed more severe inflammatory cell infiltration and less fibrosis than the former two cases did. It was suggested that the signal intensity on T(2)WI and DWI depends on the degree of inflammation and fibrosis in renal granuloma. It is currently challenging to distinguish renal granuloma from renal malignancy based on only imaging findings. Biopsies were helpful in confirming the diagnosis and avoiding unnecessary resection. Renal granuloma should be considered as a differential diagnosis when a renal mass is found in a patient with a history of intravesical BCG treatment.